Juridical Review of the Free Nutritious Eating Policy as an Effort to Fulfill Children's Right to Social Welfare - Maria Br Napitupulu (Journal of Family and Sharia, 2026)
Children's right to social welfare requires more than declaratory legal guarantees because unequal access to adequate nutrition persists and the legal position of the Free Nutritious Meal policy has not been fully examined within Indonesia's child-protection framework. This study analyzes the juridical basis and legal implications of the policy as an instrument for fulfilling children's social welfare rights. It uses normative legal research with statutory and conceptual approaches. Primary materials include the 1945 Constitution, the Child Protection Law, the Social Welfare Law, the Food Law, and regulations on the National Nutrition Agency; secondary materials comprise legal scholarship and recent studies. The materials are analyzed qualitatively through systematic interpretation and legal reasoning. The study finds that the policy has a strong constitutional and statutory foundation, reflects the welfare-state obligation to provide basic social protection, and accords with the principles of the best interests of the child and non-discrimination. Its effectiveness, however, depends on clear recipient criteria, nutritional standards, institutional coordination, accountable budgeting, complaint mechanisms, and continuous oversight. The study contributes an integrated legal construction connecting constitutional child rights, social welfare law, food law, and administrative governance. It concludes that the program should be treated as a rights-based public obligation rather than a temporary charitable measure.